2016
DOI: 10.3847/0004-637x/817/1/2
|View full text |Cite
|
Sign up to set email alerts
|

A 5 × 109 M BLACK HOLE IN NGC 1277 FROM ADAPTIVE OPTICS SPECTROSCOPY

Abstract: The nearby lenticular galaxy NGC 1277 is thought to host one of the largest black holes known, however the black hole mass measurement is based on low spatial resolution spectroscopy. In this paper, we present Gemini Near-infrared Integral Field Spectrometer observations assisted by adaptive optics. We map out the galaxy's stellar kinematics within ∼440 pc of the nucleus with an angular resolution that allows us to probe well within the region where the potential from the black hole dominates. We find that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(101 citation statements)
references
References 88 publications
17
84
0
Order By: Relevance
“…Intriguingly, while the median M bh /M sph ratio has increased, two points should be made. As warned by Merritt (2013), the importance of being able to better resolve the black hole's sphere-of-influence was illustrated with NGC 1277, whose black hole mass measurement dropped by an order of magnitude as the spatial resolution increased by an order of magnitude (van den Bosch et al 2012;Emsellem 2013;Walsh et al 2016;. Second, Batcheldor (2010) and Shankar et al (2016) have suggested that the sample of galaxies with directly measured black hole masses may reflect the upper envelope of points in the M bh -M sph diagram, because it is preferentially galaxies with a bigger black hole and thus a bigger sphere-of-influence that can have their black hole mass measured.…”
Section: Updatesmentioning
confidence: 99%
“…Intriguingly, while the median M bh /M sph ratio has increased, two points should be made. As warned by Merritt (2013), the importance of being able to better resolve the black hole's sphere-of-influence was illustrated with NGC 1277, whose black hole mass measurement dropped by an order of magnitude as the spatial resolution increased by an order of magnitude (van den Bosch et al 2012;Emsellem 2013;Walsh et al 2016;. Second, Batcheldor (2010) and Shankar et al (2016) have suggested that the sample of galaxies with directly measured black hole masses may reflect the upper envelope of points in the M bh -M sph diagram, because it is preferentially galaxies with a bigger black hole and thus a bigger sphere-of-influence that can have their black hole mass measured.…”
Section: Updatesmentioning
confidence: 99%
“…A recent example is NGC 1277, where claims of a ∼ 2 × 10 10 M SBH [53] were subsequently found to be too large by factors of 3-5 [46,66]. Indeed, beyond the Local Group, few if any galaxies show evidence for a central increase in the rms stellar velocities on the relevant spatial scales (see Figure 2.5 in [21]).…”
Section: Sbh Demographicsmentioning
confidence: 99%
“…NGC 1277 and NGC 1271 are two such compact galaxies, with NGC 1277 being widely studied over the last few years (e.g., van den Bosch et al 2012;Emsellem 2013;Walsh et al 2016;Scharwächter et al compact (R e = 2.8 kpc, M ⋆ = 1.6 × 10 11 M ⊙ ), highdispersion (σ ⋆ = 308 km s −1 ) galaxy found through the HET Massive Galaxy Survey. Yıldırım et al (2015) presented wide-field integral-field spectroscopy of Mrk 1216, and constructed axisymmetric Schwarschild models in order to learn about the galaxy's dynamical stellar massto-light ratio and dark matter halo.…”
Section: Introductionmentioning
confidence: 99%